"NYLlNGUK" - Darno Darno (Keteg : Jurnal Pengetahuan, Pemikiran dan Kajian Tentang Bunyi, 2004)
"Nylinguk" is a musical composition, taken from the compositional  concept of bamboo music (calung), which originates from traditional  sources found in the residency of Banyumas during the era of the  lengger art form, from the 1970s until the present day. The existence  of lengger is reflected in the form of a performance of lengger calung,  using a variety of musical approaches, such as Sunda, Cirebon,  Surakarta, and Banyumas style karawitan.Key words: Tradition, Inovation, Progressive